Preparation, in vitro release, and pharmacokinetics in rabbits of lyophilized injection of sorafenib solid lipid nanoparticles - Hong Zhang; Fuming Zhang; Shijun Yan (2012)
Sorafenib solid lipid nanoparticles (S-SLN) were prepared by emulsion evaporation-solidification at low temperature. Morphology was examined by transmission electron microscope. Particle size and zeta potential were determined by laser granularity equipment. Encapsulation efficiency (EE) was detected by Sephadex gel chromatography and high-performance liquid chromatography (HPLC). The in vitro release profile of S-SLN was studied with dialysis technology. The lyophilized injection of S-SLN was prepared by freeze drying and analyzed by differential scanning calorimetry. The plasma concentration of sorafenib in blood was determined by HPLC. The solid lipid nanoparticles assumed a spherical shape with an even distribution of diameter and particle size 108.23 ± 7.01 nm (n = 3). The polydispersity index, zeta potential, and EE were determined to be 0.25 ± 0.02, -16.37 ± 0.65 mV, and 93.49% ± 1.87%, respectively (n = 3). The in vitro release accorded with the Weibull distribution model. An equal volume of 15% (w/v) mannitol performed better as the protective agent for a lyophilized injection of S-SLN with a new material phase formation. The pharmacokinetic processes of sorafenib solution and lyophilized injection of S-SLN in vivo were in accordance with the two-compartment and one-compartment models, respectively. S-SLN nanoparticles are thus considered a promising drug-delivery system.